2014
DOI: 10.1017/prp.2014.2
|View full text |Cite
|
Sign up to set email alerts
|

Colonial Debt, Resistance to U.S. Military Presence, Trustworthiness of Pro-U.S. Military Information Sources, and Support for the Military Buildup on Guam

Abstract: In this exploratory study, a representative community survey of 319 registered voters was conducted in the island of Guam to analyse the relationships between colonial debt (an internalised acceptance of colonisation), resistance to U.S. military presence, support for an impending U.S. military buildup in the island, and the perceived trustworthiness of information sources supportive of the buildup — that is, U.S. officials and the Pacific Daily News, a local newspaper. Results suggest that colonial debt was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…For reasons that are not clear to us, ideological dynamics in Puerto Rico were closely tied to epistemic motives but not to existential or relational motives. The present research contributes to work on intergroup relations and political psychology on internalized oppression and colonial ideologies (e.g., Bobowik et al, 2018;Dalisay, 2014;Sibley & Osborne, 2016) by linking these variables not only to political and economic forms of system justification, but also to preferences about Puerto Rico's political status. When adjusting for all system justification measures (Figure 2), we observed that supporters of the territorial status quo legitimized the capitalist economic system, whereas supporters of statehood legitimized the U.S. political system; both of these groups also legitimized the colonial system as a whole (Figure 1).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…For reasons that are not clear to us, ideological dynamics in Puerto Rico were closely tied to epistemic motives but not to existential or relational motives. The present research contributes to work on intergroup relations and political psychology on internalized oppression and colonial ideologies (e.g., Bobowik et al, 2018;Dalisay, 2014;Sibley & Osborne, 2016) by linking these variables not only to political and economic forms of system justification, but also to preferences about Puerto Rico's political status. When adjusting for all system justification measures (Figure 2), we observed that supporters of the territorial status quo legitimized the capitalist economic system, whereas supporters of statehood legitimized the U.S. political system; both of these groups also legitimized the colonial system as a whole (Figure 1).…”
Section: Discussionmentioning
confidence: 95%
“…This may be due to certain assumptions in mainstream psychology that treat colonialism as a historical curiosity rather than a contemporary phenomenon (Adams et al., 2018). Still, noteworthy contributions to the literature have linked colonial mentality to experiences of sexism and racism on the part of Filipina women (Felipe, 2016) and colonial debt (a sense of obligation or indebtedness to colonial powers) to support for the U.S. military presence in Guam (Dalisay, 2014). To our knowledge, the research in Guam represents the only previous study that connects colonial mentality to overtly political attitudes.…”
Section: Decolonial Approaches To Understanding and Overcoming Intern...mentioning
confidence: 99%
“…instead of continuing to be someone else's welcome mat or someone's tuntågo [subordinate]. (L. Lizama, personal communication, January 4, 2020) For Lizama, the process of critically reflecting on CHamoru history is an emotionally powerful process that, at the end of which, leads one away from feelings of what Francis Dalisay (2014) refers to as colonial debt, "a sense of loyalty to the United States" (p. 12). In a CHamoru context, being a tuntågo normally implies that one does something in the service of another, usually an elder, and can be associated with care or a sense of duty to one's family.…”
Section: Nina'lå'la': Media As a Generative Resurgent Praxismentioning
confidence: 99%
“…Yet the word takes on a different set of racial, class, and cultural implications within the example given by Lizama, where one is a subordinate to the powers of the settler state and its actors. A tuntågo, in this sense, is one who has internalized their acceptance of oppression and uncritically engages in the status quo (Dalisay, 2014).…”
Section: Nina'lå'la': Media As a Generative Resurgent Praxismentioning
confidence: 99%